Postoperative complications in rectal cancer patients are associated with delays in chemotherapy which lead to worse disease free and overall survival: Rectal cancer complications chemotherapy - Tevis, Sarah E. (2013)
OBJECTIVE: The objective of this study was to identify risk factors for delays in chemotherapy after rectal cancer surgery and evaluate the effects of delayed therapy on long term outcomes. We also sought to clarify what time frame should be used to define delayed adjuvant chemotherapy. BACKGROUND: Postoperative complications have been found to influence timing of chemotherapy in colon cancer patients. Delays in chemotherapy have been shown to be associated with worse overall and disease free survival in colorectal cancer patients, although timing of delay has not been agreed upon in the literature. STUDY DESIGN: We performed a retrospective review of a prospectively maintained rectal cancer database. Univariate analysis was used to identify risk factors for delayed chemotherapy. Kaplan Meier curves were generated to compare overall and disease free survival in patients based on complications and timing of chemotherapy. SETTINGS: This study was performed at the University of Wisconsin Hospital, Madison, WI between 1995 and 2012. PATIENTS: Patients with rectal cancer who underwent proctectomy with curative intent were included in this study. OUTCOME MEASURES: Timing of chemotherapy, 30 day complications and 30 day readmissions were the main outcome measures. RESULTS: Postoperative complications and 30 day readmissions were associated with delays in chemotherapy ≥ 8 weeks after surgery. Patients who received chemotherapy ≥ 8 weeks postoperatively were found to have worse local and distant recurrence rates and worse overall survival as compared with patients who received chemotherapy within 8 weeks of surgery. LIMITATIONS: Limitations of this study include its retrospective nature and that it was performed at a single institution. CONCLUSIONS: We found complications and readmissions to be risk factors for delayed chemotherapy. Patients who received therapy ≥ 8 weeks postoperatively had worse disease free and overall survival.